Organización interna y su influencia en el nivel de productividad de la empresa Constructora Toasan del cantón Montalvo, provincia de los Ríos - Bombosa Gaibor, Gabriela Maibel (2018)
The present research work is based on internal organization through the level of productivity, resulting in a good organization within the company structuring an organization with criteria and performance. For a good internal organization, the company has as a responsibility to implement new strategies and therefore have knowledge of it, in order to achieve the objectives of business planning and that their level of productivity increases to their performance. The outcome of this research paper decreed that maintaining a good organization within the company is a great help for those who make up the institution, so it is important to implement a manual on the internal organization of a company so improve the level of productivity.